Temperature of quasi-two-dimensional electron gases under steady-state terahertz drive - Asmar, N. G.; Cerne, J.; Markelz, A. G.; Gwinn, E. G.; Sherwin, M. S.; Campman, K. L.; Gossard, A. C. (Applied Physics Letters, 1996)
We use photoluminescence to study the time-average energy distribution of electrons in the presence of strong steady-state drive at terahertz (THz) frequencies, in a modulation-doped 125 Angstrom AlGaAs/GaAs square well that is held at low lattice temperature TL. We find that the energy distribution can be characterized by an effective electron temperature, T-e(>T-L), that agrees well with values estimated from the THz-illuminated, dc conductivity. This agreement indicates that under strong THz drive, LO phonon scattering dominates both energy and momentum relaxation; that the carrier distribution maintains a heated, thermal form; and that phonon drift effects are negligible. (C) 1996 American Institute of Physics.
ISI Document Delivery No.: TT663 Times Cited: 59 Cited Reference Count: 12 Cited References: ASMAR NG, 1995, PHYS REV B, V51, P18041, DOI 10.1103/PhysRevB.51.18041 BETHUNE DS, 1989, J OPT SOC AM B, V6, P910, DOI 10.1364/JOSAB.6.000910 CERNE J, 1995, PHYS REV B, V51, P5253, DOI 10.1103/PhysRevB.51.5253 CONWELL E, 1967, SOLID STATE PHYS S, V9 GUPTA R, 1992, PHYS REV B, V46, P7745, DOI 10.1103/PhysRevB.46.7745 HEYMAN JN, 1994, PHYS REV LETT, V72, P2183, DOI 10.1103/PhysRevLett.72.2183 KOMIYAMA S, 1985, PHYS REV B, V32, P5532, DOI 10.1103/PhysRevB.32.5532 MARKELZ AG, 1994, SOLID STATE ELECTRON, V37, P1243, DOI 10.1016/0038-1101(94)90399-9 MARKELZ AG, 1995, THESIS U CALIFORNIA SHAH J, 1984, APPL PHYS LETT, V44, P322, DOI 10.1063/1.94739 SHAH J, 1978, SOLID STATE ELECTRON, V21, P43, DOI 10.1016/0038-1101(78)90113-2 YANG CH, 1985, PHYS REV LETT, V55, P2359, DOI 10.1103/PhysRevLett.55.2359 Asmar, NG Cerne, J Markelz, AG Gwinn, EG Sherwin, MS Campman, KL Gossard, AC Sherwin, Mark S/Q-4762-2017 Sherwin, Mark S/0000-0002-3869-1893; Markelz, Andrea/0000-0003-0443-4319 59 7 Amer inst physics Woodbury
Keywords: hot-electrons; Physics